1996
DOI: 10.1002/(sici)1097-0266(199603)17:3<219::aid-smj806>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Reference Point Theory

Abstract: How can executives achieve a match between expected external environmental conditions and internal organizational capabilities that facilitates improved performance? This paper argues that a firm's choice of ‘reference points’ can help achieve strategic alignment capable of yielding improved performance and potentially even a sustainable competitive advantage. Building upon prospect theory and other relevant theoretical perspectives, the strategic reference point (SRP) matrix is developed. A firm's SRP consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
305
1
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(322 citation statements)
references
References 76 publications
7
305
1
4
Order By: Relevance
“…Similar to others advocating a balanced scorecard approach that examines financial, customer, internal business, and innovation/learning-based goals in family businesses (Craig & Moores, 2005), we argue for the importance of incorporating diverse goals into understanding the overall performance of family businesses. Following strategic reference point theory, which states that businesses use internal, external, and/or time-related referents to gauge performance (Fiegenbaum, Hart, & Schendel, 1996), we argue that such referents can be identified using content analysis of narratives and that these may be reasonable indicators of objective performance (Short & Palmer, 2003). Below we more extensively discuss the method demonstrated in this article and identify several areas where future research can use this method to further our understanding of privately held family businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to others advocating a balanced scorecard approach that examines financial, customer, internal business, and innovation/learning-based goals in family businesses (Craig & Moores, 2005), we argue for the importance of incorporating diverse goals into understanding the overall performance of family businesses. Following strategic reference point theory, which states that businesses use internal, external, and/or time-related referents to gauge performance (Fiegenbaum, Hart, & Schendel, 1996), we argue that such referents can be identified using content analysis of narratives and that these may be reasonable indicators of objective performance (Short & Palmer, 2003). Below we more extensively discuss the method demonstrated in this article and identify several areas where future research can use this method to further our understanding of privately held family businesses.…”
Section: Discussionmentioning
confidence: 99%
“…To be effective, a vision must be unambiguous, public, and widely understood, making it highly codified in nature (Hamel and Prahalad, 1989;Fiegenbaum, Hart, and Schendel, 1994). However, "saying it" and "doing it" are two different things: Developing a shared vision of sustainable development would seem to require skilful leadership and an empowering social process, reaching deep into the management ranks (Senge, 1990).…”
Section: Insert Figure 4 About Herementioning
confidence: 99%
“…Furthermore, shared vision might provide the essential context within which process-based initiatives can be embedded (Hamel and Prahalad, 1989). Efforts to develop new process skills without a sense of purpose or direction would thus seem to be less effective than process development driven by a shared vision (Senge, 1990;Fiegenbaum, Hart, and Schendel, 1994).…”
Section: Implementing the Natural Resource-based Viewmentioning
confidence: 99%
“…Performance has triggered organisational search because performance above or below aspirations has determined the boundary between success and failure (Fiegenbaum, Hart, and Schendel 1996;Greve 2003;Lant and Mezias 1990;Lant, Milliken, and Batra 1992). Case study research has demonstrated that performance shocks can have the effect of overcoming inertial forces resistant to exploration activities and can stimulate organisational renewal.…”
Section: Exploration and Exploitation Within And Across Intra-organismentioning
confidence: 99%